PENGARUH MANAJEMEN LABA DAN UKURAN PERUSAHAAN TERHADAP BIAYA MODAL EKUITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lisa Kurnia; M. Yasser Arafat (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
Lisa Kurnia, 2015. The influence of the earning management and firm size againts the cost of equity capital at the manufacturing companies listed on the Indonesia Stock Exchange 2010-2012 period. This research aimed to (1) find out the influence of the earning management againts the cost of equity capital (COEC) at the manufacturing companies listed on the Indonesian Stock Exchange 2010-2012 period, (2) find out the influence of companies size againts the cost of equity capital (COEC) at the manufacturing companies listed on the Indonesian Stock Exchange 2010-2012 period. The population in the research were manufacturing companies of consumption goods industry which listed Indonesian stock exchange 2010-2012. Sample selection technique used was purposive sampling method. The sample of this research consist of 81 manufacturing company . The method used was multiple linear regression analysis. Based on the t test result show that earnings management and company size significantly and negatively related to the cost of equity capital. Keywords: earnings management, company size, cost of equity capital